2(6-2b)=0

Simple and best practice solution for 2(6-2b)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6-2b)=0 equation:


Simplifying
2(6 + -2b) = 0
(6 * 2 + -2b * 2) = 0
(12 + -4b) = 0

Solving
12 + -4b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -4b = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -4b = 0 + -12
-4b = 0 + -12

Combine like terms: 0 + -12 = -12
-4b = -12

Divide each side by '-4'.
b = 3

Simplifying
b = 3

See similar equations:

| 2(3m-10)= | | 5y+2=3y-1 | | 2(3m+5)= | | 3x+6=89-5x | | -27=x+19 | | -2(5-3m)= | | 3(7)/3= | | 3z-(10)=1 | | log(12x^4)-log(2x^3)=2 | | 4(5+7b)+6b=-252 | | cos(x)=-0.5 | | 5ln(x-11)-3=7 | | 8x^2-6x-3=0 | | 3(5-15)=m-5 | | 3x+25=12x+83 | | 3a-1(-1)=-5 | | 4(3y-3)-2y=-9 | | 4v+-3v-4=13 | | 6x^2-2x^3-4x=0 | | 2k-16-10k=-2k | | 207-7x=38x+22 | | -12-3+9= | | 6(x+4)-(2x-8)= | | 5-(-8)=x | | y^2-5y-3=0 | | 5(d-6)+6= | | 2m^3-5m^2-12m=0 | | (2x-3)+(x^2-4x)=180 | | 5x^2+3x-16=32-31x | | -3u+8=14 | | c-(-2)=68 | | 3y+4=-20 |

Equations solver categories